A proposed course of study in Language arts I for effective living for the U.P. Preparatory High School - Botor, Celeste Ordas 1928- (University of the Philippines], 1958)
Recommendations of workshops, freedom to plan and exercise self-direction in teaching, as well as favorable conditions and support by the school administration, led directly to this study, which is mainly concerned in knowing the nature of the language arts course for the first year students of the UP Preparatory High School who intend to go to college.